Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.9755/ejfa.2017.v29.i10.1260
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of drought resistance in Iris germanica L. based on subordination function and principal component analysis

Abstract: Drought is one of the major environment stresses that have a wide range of impact on plants. In this study, seven physiological indexes including the content of soluble protein (SP), chlorophyll (Chl) and malondialdehyde (MDA), superoxide dismutase (SOD) and peroxidase (POD) activities, leaf relative water content (RWC), rate of water loss (RWL) from excised leaves were measured in leaves of Iris germanica before and after the drought treatment. It was found that the content of MDA and SP, POD and SOD activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…In rice, corn and wheat, PCA is used for drought resistance analysis and evaluation, and relevant drought resistance indicators have been determined. PCA can explain and describe the important indicators of drought resistance and salt tolerance in germplasm (Bo et al, 2017;Negrão et al, 2017;Kakar et al, 2019). Ayalew et al (2011) identified three principal components through PCA, which accounted for 70% of the total variation in 14 agronomic traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rice, corn and wheat, PCA is used for drought resistance analysis and evaluation, and relevant drought resistance indicators have been determined. PCA can explain and describe the important indicators of drought resistance and salt tolerance in germplasm (Bo et al, 2017;Negrão et al, 2017;Kakar et al, 2019). Ayalew et al (2011) identified three principal components through PCA, which accounted for 70% of the total variation in 14 agronomic traits.…”
Section: Discussionmentioning
confidence: 99%
“…Drought stress reduces yield because it affects crop growth and physiological metabolism (Nagy et al, 2013;Liu et al, 2015), which includes many drought resistance indicators, and it is difficult to consider all indicators when analyzing macropopulations. However, PCA can be used to determine the weight of each indicator and finds some principal components that can control all variables (Ali et al, 2014;Chen et al, 2014;Wijewardana et al, 2016;Bo et al, 2017;Füzy et al, 2019). It can reduce the number of measurement indicators and improve measurement efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The drought tolerance responses of different species to a specific indicator will not necessarily be the same. A single indicator cannot comprehensively or accurately reflect the strength of drought tolerance (Wei, Fu, Qin, Xing, & Wang, 2017). Therefore, this study used RM, RL, RA, RV, tips, LA, and 10 other indicators to identify the drought tolerance of the different species; these indicators have been widely used (Qiao et al, 2019;Zhang, Shi, Wang, & Zhao, 2018).…”
Section: Drought-resistant Species Selection Based On Root Trait Prmentioning
confidence: 99%
“…The method of membership function was used to comprehensively evaluate the drought tolerance and saline-alkali tolerance of each maize varieties during mature period (Chen 2002, Shi et al 2010, Bo et al 2017.…”
Section: Methodsmentioning
confidence: 99%